Determination of residual enrofloxacin in eggs due to long term administration to laying hens: Analysis of the consumer exposure assessment to egg derivatives - Teglia, Carla Mariela (2021)
The use of the antibiotic enrofloxacin (ENR) in poultry is controversial. A high-performance liquid chromatography coupled to fast-scanning fluorescence detection (HPLC-FSFD) method for the determination of ENR in egg white, egg yolk, and lyophilized samples was developed. In a first analysis, the long-term administration of ENR (100 days) to laying hens was carried out to determine its presence in egg white, yolk, or both. The predominance of ENR was observed in egg white and variations in the weight of egg white and eggshell was evidenced, showing a potential problem in the industry. Eventually, the presence of ENR was confirmed in commercial lyophilized egg white samples in concentration values around 350 μg/kg. The consumer exposure assessment was estimated for children, adolescents, and adults. The result displayed that, in an intake of lyophilized egg white with food-producing animals, the %ADI exceeds 100%, showing toxicological levels.